The Effect of Household versus Enterprise Credit on Economic Growth in Turkiye - İSMİÇ, Betül; ŞEN, Sedef (Cumhuriyet University, 2023)
Although theoretical predictions suggest distinct impacts of household and enterprise credit on the economy, the empirical literature has predominantly relied on aggregate indicators of total bank lending to the private sector. This study aims to empirically assess the effects of total bank credit on the private sector as well as enterprise (or business) and household credit markets on economic growth. The empirical study is based on a time series approach called ARDL cointegration to reveal the long and short-run relationships between related variables. An annual time series data from 1986 to 2021 is applied for Turkiye. Empirical results show that enterprise credit has a positive impact on economic growth, whereas household credit does not affect economic growth. The findings also show that the total amount of banking credit given to the private sector does not affect economic growth. Furthermore, it is presented that there is a two-way causality for enterprise credit and economic growth in the short and long-run. The lending structure determines how much financial development impacts economic growth. Our findings explain that it is not relevant how much money financial institutions lend, but to whom and for what purposes it is lent is quite significant in Turkiye.
Keywords: Finans; HF1-6182; financial development; enterprise credits; Commerce; household credits; economic growth; Finance; financial development; economic growth; household credits; enterprise credits; 8. Economic growth; 1. No poverty